Roles of p53 in Herpes Simplex Virus 1 Replication - Maruzuru, Yuhei (American Society for Microbiology, 2013)
p53 is a critical factor in the cellular response to a broad range of stress factors through its ability to regulate various cellular pathways. In this study, tandem affinity purification of transiently expressed herpes simplex virus 1 (HSV-1) regulatory protein ICP22 coupled with mass spectrometry-based proteomics technology and subsequent analyses showed that ICP22 interacted with p53 in HSV-1-infected cells. In p53(−/−) cells, replication of wild-type HSV-1 was reduced compared to that in parental p53(+/+) cells, indicating that p53 had a positive effect on HSV-1 replication. In contrast, the levels of viral replication of an ICP22-null mutant virus were similar in both p53(−/−) and p53(+/+) cells. At 2 h postinfection, the level of expression of ICP27, an essential viral regulatory protein, in p53(−/−) cells infected with wild-type HSV-1 or the ICP22-null mutant virus was lower than in p53(+/+) cells. In contrast, at 18 h postinfection, the level of expression of ICP0, a critical viral regulatory protein, in p53(−/−) cells infected with the ICP22-null mutant virus was higher than in p53(+/+) cells, although the levels of ICP0 expression in p53(−/−) and p53(+/+) cells infected with wild-type HSV-1 were almost identical. These results suggested that p53 overall promoted HSV-1 replication and that p53 played both positive and negative roles in HSV-1 replication: upregulating ICP27 expression very early in infection and downregulating ICP0 expression later in infection, which was antagonized by ICP22.